2013
DOI: 10.1080/10158782.2013.11441516
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of carbapenem resistance genes inAcinetobacter baumanniiisolated from clinical specimens obtained from an academic hospital in South Africa

Abstract: Original Research: Prevalence of carbapenem resistance genes in Acinetobacter baumannii isolated from clinical specimens Acinetobacter baumannii is an important cause of hospital-acquired infections. The occurrence of carbapenem resistance that is caused by the carbapenem-hydrolysing class D β-lactamases and the metallo-β-lactamases (MBLs) limits the range of therapeutic alternatives in treating A. baumannii infections. In this study, two multiplex polymerase chain reactions were performed to screen for both c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
35
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 24 publications
7
35
3
Order By: Relevance
“…The study reported resistance to imipenem at 86%; meropenem at 86%; cefepime at 90% and ceftazidime at 89%. Our study results revealed higher resistance prevalence compared to a similar study by Kock et al, [5]. In their study also conducted in Pretoria (2008), they reported resistance to imipenem at 59 %; meropenem at 63 %; cefepime at 62 % and ceftazidime at 45 %.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…The study reported resistance to imipenem at 86%; meropenem at 86%; cefepime at 90% and ceftazidime at 89%. Our study results revealed higher resistance prevalence compared to a similar study by Kock et al, [5]. In their study also conducted in Pretoria (2008), they reported resistance to imipenem at 59 %; meropenem at 63 %; cefepime at 62 % and ceftazidime at 45 %.…”
Section: Discussionsupporting
confidence: 52%
“…In their study also conducted in Pretoria (2008), they reported resistance to imipenem at 59 %; meropenem at 63 %; cefepime at 62 % and ceftazidime at 45 %. The prevalence of drug resistance to antimicrobials other than the polymixin class in A. baumannii isolates has increased to 100% over the years [5; 17]. To date, Colistin has remained susceptible in all the A. baumannii isolates collected in this region.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…95 blaOXA-51, blaOXA-23, and blaOXA-58 are so far the main CHDLs found in A. baumannii isolates with resistance to all b-lactams in South Africa. 14,32,42 The first description of blaOXA-181 in South Africa was in K. pneumonia, 18 and the most reported blaOXA-48-like genes have been found in K. pneumonia (Supplementary Table S1), and in a few cases, E. coli and E. cloacae, where they mediated resistance to all antibiotics except amikacin, tigecycline, and colistin. 18,19,21 blaVIM genes have been identified in several P. aeruginosa, A. baumannii, and E. cloacae isolates, whiles blaIMP is commonly identified in E. cloacae.…”
Section: South Africamentioning
confidence: 98%